Multifunctional exosome-driven pancreatic cancer diagnostics and therapeutics - Sitong Zhang; Danyang Li; Yingjia Liu; Chunlian Qin; Lingjun Tong; Lizhou Xu (Extracellular Vesicle)
Pancreatic cancer (PC) remains one of the most common causes of cancer death. The overall survival rate of PC is relatively low. PC frequently presents in patients with nonspecific symptoms at the localized stage and PC patients are mostly diagnosed at an advanced stage. Therefore, the early diagnosis and treatment of suspected PC patients with or without symptoms are of significant importance for improving both patient prognosis and survival rate. Exosomes are smaller nano-sized extracellular vesicles that are secreted from cells for cellular communication. Exosomes are increasingly recognized as a promising new generation of biomarkers for PC detection, especially in the early stages. Owning to their carriage of endogenous proteins, nucleic acids, and other contents from releasing parent cells, such as cancer cell, which exosomes are believed to be tightly associated with clinically relevant cancer processes. Meanwhile, exosomes are potential drug delivery systems for therapeutics due to their natural origin and their ability to encapsulate biological molecules, including proteins and RNAs, within the double-layer lipid membrane. In this review, the multifunctional roles of exosomes in PC are summarized. Moreover, we further discuss the novel exosome-based diagnostic and therapeutic strategies for PC. Finally, the future perspective on using exosomes to facilitate PC diagnosis and therapeutics is highlighted.